Information literacy in the academic context: global trends and local issues - Špiranec, Sonja; Toth, Tibor; Banek Zorica, Mihaela (2009)
Information literacy is generally perceived as the spiritus muovens of learning processes, reflecting the premise of information as the basic building block of education. This idea gained relevance and new facets with the proliferation of the Web 2.0, which has brought about new, speculative and concerning issues. In the first part of the paper the authors will discuss the importance of information literacy in the higher education sector. They will particularly discuss and re-examine the question what it has meant to be information literate in the print era, the digital era and in the context of the Web 2.0. Taking conceptual shifts between those different information ages as a point of departure, the particular cluster of competencies needed today to support educational processes in the higher education sector will be identified. After commenting global issues the authors will present preliminary results from a local (national) survey about the inclusion and integration of information literacy elements into Croatian new higher education (i.e. Bologna) curricula.
Projekt MZOS
ENG